2016
DOI: 10.3390/nu8120758
|View full text |Cite
|
Sign up to set email alerts
|

Patient Survival and Costs on Moderately Restricted Low-Protein Diets in Advanced CKD: Equivalent Survival at Lower Costs?

Abstract: The indications for delaying the start of dialysis have revived interest in low-protein diets (LPDs). In this observational prospective study, we enrolled all patients with chronic kidney disease (CKD) who followed a moderately restricted LPD in 2007–2015 in a nephrology unit in Italy: 449 patients, 847 years of observation. At the start of the diet, the median glomerular filtration rate (GFR) was 20 mL/min, the median age was 70, the median Charlson Index was 7. Standardized mortality rates for the “on-diet” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
(64 reference statements)
0
19
0
1
Order By: Relevance
“…The relative mortality risk in the on-diet cohort was significantly lower in comparison with various dialysis populations (United States Renal Data System (USRDS): relative risk—RR: 0.44 (CI 0.36–0.54); Italian Dialysis Registry-RR 0.73 (CI 0.59–0.88) and French Dialysis Registry-RR: 0.70 (CI 0.57–0.85)). A survival advantage was also observed in younger patients (age < 65 years) on dialysis, while mortality rates for older patients were equivalent to those recorded in the two European registries, and lower than those in the USRDS [100]. Their another study revealed that patient survival was higher on a vegan, supplemented diet (low-protein diet supplemented with keto analogues; LPD-KA), while renal survival was better on a diet based on aproteic commercial food (low-protein diet supplemented "aproteic" commercial food; LPD-ACF) [101].…”
Section: Various Types Of Dietmentioning
confidence: 91%
See 1 more Smart Citation
“…The relative mortality risk in the on-diet cohort was significantly lower in comparison with various dialysis populations (United States Renal Data System (USRDS): relative risk—RR: 0.44 (CI 0.36–0.54); Italian Dialysis Registry-RR 0.73 (CI 0.59–0.88) and French Dialysis Registry-RR: 0.70 (CI 0.57–0.85)). A survival advantage was also observed in younger patients (age < 65 years) on dialysis, while mortality rates for older patients were equivalent to those recorded in the two European registries, and lower than those in the USRDS [100]. Their another study revealed that patient survival was higher on a vegan, supplemented diet (low-protein diet supplemented with keto analogues; LPD-KA), while renal survival was better on a diet based on aproteic commercial food (low-protein diet supplemented "aproteic" commercial food; LPD-ACF) [101].…”
Section: Various Types Of Dietmentioning
confidence: 91%
“…Piccoli et al [100] in their study analyzed the impact of moderately restricted low-protein diets on the survival of patients with advanced CKD. The relative mortality risk in the on-diet cohort was significantly lower in comparison with various dialysis populations (United States Renal Data System (USRDS): relative risk—RR: 0.44 (CI 0.36–0.54); Italian Dialysis Registry-RR 0.73 (CI 0.59–0.88) and French Dialysis Registry-RR: 0.70 (CI 0.57–0.85)).…”
Section: Various Types Of Dietmentioning
confidence: 99%
“…Indeed, several randomized controlled trials (RCTs) [8,9] and observational studies [10,11] have proved that sVLPDs and sLPDs can delay the initiation of dialysis and slightly retard the decline of renal function. Moreover, in those who can adhere to the treatment and frequent follow-up of nutritional status, dietary therapy has been shown not to result in adverse effects during treatment [12,13] or after dialysis initiation [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…The patients are followed-up by the nephrology and dietetics group throughout the whole process of protein reduction; moreover, the patients who do not undergo a protein restricted diet are also followed-up to timely identify and try to compensate for the eventual signs of malnutrition. This multiple-choice stepwise approach represents an adaptation to French dietary patterns of a “diet system” previously set up in Italy, a country in which it is possible to rely on widespread acceptance of a Mediterranean baseline pattern, and reduction of protein intake is facilitated by the availability of protein-free commercial food, provided free of charge to CKD patients (Figure 3) [25,33,34].…”
Section: Methodsmentioning
confidence: 99%
“…Previous experience with a multiple-choice diet system, developed in a northern Italian setting, in which Mediterranean dietary patterns are widespread, showed that an approach offering different options, at various levels of protein restriction, produced favorable results in elderly and diabetic patients [33,34].…”
Section: Introductionmentioning
confidence: 99%